Study of women's experiences of miscarriage in South Africa - Ncube, Nobukhosi (My University, 2018)
Many pregnancies end in miscarriage, making this a common event in the lives of pregnant women. Before the 20th week of pregnancy, bleeding occurs in a fifth of documented pregnancies and more than a half of these pregnancies are miscarried (Everett 1997). Miscarriage is both a medical and a social event (Opitz, 1987, Letherby, 1993, Van der Sijp 2010). Miscarriage as a social event is presented by the role of social interactions in shaping miscarriage experiences. Most women seek medical health care after the occurrence of a miscarriage, which transforms the experience into a medical event (Pincombe et al., 2015). Although a miscarriage may be a life-changing event, there is a likelihood of a successful pregnancy following a miscarriage (Winston 2013, Van den Akker, 2012). Miscarriages may embody various connotations. A miscarriage event is a potentially life-changing event (Letherby, 1993), therefore deserving of sociological analysis. The perspective used in this study is that miscarriage is a social construct, which is constructed from both those who experience it and from the medical perspective as women interact with the medical arena. This research presents a narrative inquiry into the stories of ten women who have experienced miscarriage and are between the ages of 19-45 from different cultural and racial backgrounds, along with the expert knowledge of three health care practitioners who have worked in the maternal health care sector. Semi-structured, in-depth interviews were used as narrative guidelines for women who have experienced miscarriages and to gather expert knowledge of healthcare professionals on standard procedures in dealing with miscarriages in healthcare settings. The snowballing sampling technique was used to identify the participants for this study. Participation in this study has been voluntary and informed by continued consent. This research will completely anonymize the participants by taking out any information that might reveal the identity of the participants and the medical health care institutions they either attended or work in. Women’s emotional experiences following a miscarriage are at the center of how they articulate their miscarriage experiences and navigate through their feminine identities following a miscarriage experience, hence a need for women’s emotional needs to be met and highly prioritized following a miscarriage event. Maternal health care in South Africa has transformed for better over the years, although miscarriages still account for maternal deaths. Medical health care has been a primary source of health care for most women in an event of a miscarriage. Women’s relationship with their partners or spouses following a miscarriage event is essential for recovery, healing, and coping. Support from people one cares about, be it family, spousal support and support from one’s inner circle of friends and social associations, is essential in shaping up women’s miscarriage experiences. Cultural interpretations and value systems still play a role in informing women’s understandings of a miscarriage.
A thesis submitted for the degree of Master of Arts in Health Sociology at the Faculty of Humanities of the University of the Witwatersrand, Johannesburg, 2018
Keywords: Miscarriage--South Africa--Psychological aspects; Women--Pregnancy--South Africa